The Democratic character values formation in the School of the Ministry Defense of the Republic Indonesia - Catyaningsih, Riyatmi; Priyanto, Agustinus Sugeng; Subagyo, Subagyo (JESS (Journal of Educational Social Studies), 2022)
Democratic character values formation is a way to foster a sense of tolerance and respect for diversity. The purpose of the study was to determine the formation of democratic character values in schools with military backgrounds. The study was conducted at SMA Taruna Nusantara Magelang, using qualitative research methods. The data was obtained through interviews and filling out questions using google form. The results of the study indicate that democratic values are formed through the process of education, parenting, training, and are integrated in daily life supported by a special school system and curriculum. Taruna Nusantara High School students conduct the organization like an election in which each candidate for chairman and section candidates makes speeches and campaigns to get support from friends through a dialogical campaign, students are given the freedom to make posters and give speeches in order to seek support. This research is useful for the Ministry Defense of the Republic Indonesia to implement democratic character education evenly.